MiR-22-3p modulated the antioxidant activity of curcumin via targeting the cardiolipin synthase gene CRLS1 in LO2 cells. (May 2023) - Sun, Xiaoting; Li, Yuanyuan; Lin, Yanqi; Mei, Yuanyuan; Lin, Lingli; Ho, Kuo-Ting; Huang, Kaiyan; Zhan, Jialin; Chen, Chaoxiang; Zeng, Jun; Wu, Daren; Li, Jian; et al.
Graphical abstract: Highlights: Curcumin enhanced cellular antioxidant capacity via downregulating miR-22-3p. miR-22-3p reduced cellular antioxidant capacity via inhibiting CRLS1 expression. The redox regulation of miR-22-3p/ CRLS1 was attributed to mitochondrial modulation. Abstract: The antioxidant activity of curcumin has been extensively investigated for years. However, its molecular function mechanism remained unclear. Our preliminary study showed that curcumin downregulated miR-22-3p expression. This study aimed to address whether miR-22-3p mediated the antioxidant activity of curcumin and the possible action mechanism. The results showed that miR-22-3p repression increased the total cellular antioxidant capacity and enhanced the endogenous antioxidant enzyme system of LO2 cells. In addition, miR-22-3p-deteriorated cellular antioxidant capacity was prevented by curcumin pretreatment. Moreover, miR-22-3p inhibition significantly improved mitochondrial function and biogenesis. Further investigation demonstrated that a mitochondrial key regulator, the cardiolipin synthase gene ( CRLS1 ), was targeted and downregulated by miR-22-3p. CRLS1 overexpression also significantly improved cellular antioxidant capacity and enhanced mitochondrial function and biogenesis in LO2 cells. Taken together, all these data suggested that miR-22-3p modulated the antioxidant effect of curcumin via targeting CRLS1, which may provide novel insights into miRNA-mediated antioxidant mechanism of curcumin.